(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the association between cold atmospheric plasma therapy and recovery of perineal sutures following vaginal delivery. Methods: A prospective cohort study was conducted among 140 primiparous women with second-degree perineal sutures after vaginal delivery, including 70 women receiving cold plasma therapy and 70 receiving routine care. Pain intensity was assessed using the Visual Analog Scale (VAS), and perineal wound recovery was evaluated using the REEDA scale on postpartum days 1, 2, 3, and 14. Results: The two groups were comparable in age, BMI, medical comorbidities, and neonatal birth weight, but differed in occupational distribution. No significant differences in VAS or REEDA scores were observed on days 1 and 2. From day 3 to day 14, the plasma therapy group had significantly lower VAS and REEDA scores than the routine care group. After adjustment for BMI, medical comorbidities, neonatal birth weight, and occupation, cold plasma therapy remained associated with lower VAS and REEDA scores on days 3 and 14. No cases of perineal infection were recorded in either group. Conclusion: Cold atmospheric plasma therapy was associated with faster improvement in pain intensity and perineal suture recovery during the early postpartum period. Further studies with more rigorous designs and longer follow-up are needed to confirm its effectiveness and fully evaluate its safety.